Paraneoplastic syndrome in lung cancer - Dumansky, Yu.V.; Syniachenko, O.V.; Stepko, P.A.; Yehudina, Ye.D.; Stoliarova, O.Yu. (Experimental Oncology, 2018)
Aim: To study the nature of different variants of paraneoplastic syndrome (PNPS) in lung cancer, taking into account the features of the tumorous process and the complications of radiochemotherapy. Patients and Methods: We performed an analysis of the data of 1,669 patients with lung cancer aged between 24 and 87 years, among whom there were 89% of men and 11% of women. The ratio of small cell and non-small-cell histological variants of the lung cancer was 1: 4, IB, IIA, IIB, IIIA, IIIB and IV stages of cancer — 1:2:6:58:43:57. Results: PNPS developed in 16% of the lung cancer patients, in these patients we have detected a marked increase in the disease incidence in women, the peripheral form of the tumor, the apical variant of Pancoast — Tobias and adenocarcinoma, but no cases of the median lower localization of the tumor. The number of the upper lobar pathology was decreased, while the severity of the cancer was significantly greater, which more often occurred with exudative pleurisy, germination of the tumor into the chest wall and compression of the upper vena cava. The 21 components of PNPS pathology were established. We distributed them conditionally into the musculoskeletal system lesions, variants of skin vasculitis and autoimmune processes, the nature of which depended on the localization and course of the tumorous process, its histological variation and severity of the course. Moreover, PNPS negatively affected the development of radiochemotherapy complications and worsened survival rate. Conclusions: The course of PNPS in lung cancer is highly diverse, being a risk factor for a severe tumorous process that worsens the survival of patients. Key Words: lung cancer, paraneoplastic syndrome.